Utilizing Organizational Culture to Form User Compliance through Systems Development - Muhamad Rezza Vahlevy; Irvan Noormansyah; Erna Lovita (International Journal of Religious and Cultural Studies, 2023)
This study aims to reveal how organizational culture forms users compliance of internal control systems through the development of accounting information systems. An ethnomethodological approach as a form of qualitative research method was employed. The results show that the development of accounting information systems in companies is coercive, so system users must take the initiative to find out what changes exist during development process. The separation of duties is one of the changes that occurs in the structure in the finance department which is enough to help the company in maintaining company assets and avoiding human error and fraud.